2019
DOI: 10.21608/ejh.2019.17411.1174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effect of experimentally induced hyperthyroidism and hypothyroidism on the parotid gland in adult male albino rats

Abstract: Introduction:Thyroid dysfunctions are considered one of the most important endocrine disorders. Alterations in the level of thyroid hormones cause various subclinical or clinical manifestations. Salivary glands act as the biological media for food and the first line of defense for oral cavity and teeth. Any alterations in their integrity and activity can affect the patient's health. Aim: This study aimed to compare the possible histo-functional alterations that may occur in the parotid gland structure in an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…In the present study, the development of hyperthyroidism was confirmed biochemically and statistically as the level of TSH decreased significantly as compared to the control groups. These changes were in agreement Hashem and Saad (12) . That meant that hyperthyroidism was well established experimentally.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the development of hyperthyroidism was confirmed biochemically and statistically as the level of TSH decreased significantly as compared to the control groups. These changes were in agreement Hashem and Saad (12) . That meant that hyperthyroidism was well established experimentally.…”
Section: Discussionsupporting
confidence: 90%
“…Hashem and Saad (12) observed several vacuoles in the acini of the parotid in hyperthyroid rats and they explained this by lipid peroxidation and oxidative stress that led to damage of cell membrane, increase in water content and hydropic degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that people suffering from thyroid hormone deficiency exhibit a wide range of clinical symptoms, including neurological impairment, difficulty in memory and concentration, and depression (Samuels and Bernstein 2022 ). Experimentally induced hypothyroidism resulted in growth and structural abnormalities of the neurons in the cortex and hippocampus, and impaired neurological function of neonatal rats (Talhada et al 2019 ; Hashem and Saad 2020 ). There is a connection between hypothyroidism and a decrease in long-term potentiation (Głombik et al 2021 ) and deterioration of memory and learning capacity (Alzoubi et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were treated with 1.2 mg/kg of Carbimazole for 14 days prior hypoxia and Ginkgo biloba and Levothyroxine treatment according Al‐Shaikh et al (2014); Hashem and Saad (2020); Mohammed et al (2022); Adebayo, Aduema, et al (2022); Adebayo, Asiwe, et al (2022), but with slight modification to develop hypothyroidism. After the completion of the hypothyroidism induction, the mice were carefully selected and portioned into four (Adebayo et al, 2021) group excluding two (Adebayo, Aduema, et al, 2022) euthyroid mice groups which were taken as the normal and hypoxic stress control.…”
Section: Methodsmentioning
confidence: 99%